2018
DOI: 10.12820/rbafs.23e0016
|View full text |Cite
|
Sign up to set email alerts
|

Agregação de comportamentos de risco à saúde de escolares da rede pública de Jequié, Bahia, Brasil

Abstract: O objetivo deste estudo foi estimar as prevalências de comportamentos de risco à saúde, de forma isolada e agregada, e analisar fatores associados. Tratou-se de estudo epidemiológico transversal, com amostra representativa de escolares de 14 a 20 anos de idade (n = 1.170) do ensino médio da rede pública, Jequié, Bahia, Brasil. Os comportamentos de risco observados foram: níveis insuficientes de atividade física, comportamento sedentário, consumo inadequado de frutas e verduras e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 3 publications
0
6
0
1
Order By: Relevance
“…In the Northeast region of Brazil, Tassitano et al 9 showed a prevalence of approximately 9% for the presence of three or more risk factors. The most recent study involving northeastern students showed a prevalence value near to 8% for the presence of three or more modifiable risk factors 11 . In contrast, a survey of young Canadians (10-17 years) of both sexes showed 37% of the sample had three or more risk factors for chronic diseases 20 .…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…In the Northeast region of Brazil, Tassitano et al 9 showed a prevalence of approximately 9% for the presence of three or more risk factors. The most recent study involving northeastern students showed a prevalence value near to 8% for the presence of three or more modifiable risk factors 11 . In contrast, a survey of young Canadians (10-17 years) of both sexes showed 37% of the sample had three or more risk factors for chronic diseases 20 .…”
Section: Discussionmentioning
confidence: 98%
“…School administrative status (public and private) is an inherent feature of the Brazilian basic education system. However, previous school-based studies that investigated the clustering or simultaneity of risk factors in young Brazilian students have neglected this fundamental feature 9,11,14 . The exception was the Adolescent Nutritional Assessment Longitudinal Study 23 , which investigated the co-occurrence of behavioral risk factors for NCDs in students from public and private schools in the metropolitan region of Rio de Janeiro (non-probabilistic sample).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations